Pengaruh Media Sosial terhadap Perilaku Konsumtif Mahasiswa - Dini Alfitriyani (Jurnal Terekam Jejak, 2023)
Student consumptive behavior can be described through several aspects of individual interests, in the current era the use of social media will influence individuals in choosing shopping choices. Social media does not only function to seek entertainment, for education, work, or study, but this research underlines the use of social media in shopping aspects. This study uses 2 instruments to see the effect between variables and uses a cross sectional survey method. There were 24 respondents who were collected with an age range of 16-24 years to describe student behavior in using social media towards consumptive behavior. This research describes the use of social media and consumer behavior by students. There are 8 questions from social media variables and there are 8 questions and statements totaling 8 from consumptive behavior variables. Especially on the question "do you often feel that social media makes it easier to get information for shopping?" in the accumulation that is seen is 50% very suitable and 50% suitable. This means that 24 respondents stated that social media had an effect on the shopping information they got. From the description of the use of social media, it can be concluded that all respondents agree with the use of social media every day and agree that social media can provide more information about shopping. From the conclusions that can be drawn is the purpose of using social media for the benefit of seeking information, working, shopping, for education, and for entertainment only. The factor that most influences students when shopping through social media is related to easy access to shopping information, promotions or discounts, and the effectiveness and efficiency of time when shopping through social media which will increase student consumptive behavior.